2021
DOI: 10.1038/s41436-021-01126-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide investigation identifies a rare copy-number variant burden associated with human spina bifida

Abstract: Purpose Next-generation sequencing has implicated some risk variants for human spina bifida (SB), but the genome-wide contribution of structural variation to this complex genetic disorder remains largely unknown. We examined copy-number variant (CNV) participation in the genetic architecture underlying SB risk. Methods A high-confidence ensemble approach to genome sequences (GS) was benchmarked and employed for systematic detection of common and rare CNVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Greater power may be gained from combining gene enrichment by deleterious variants along with damaging structural variation (e.g. CNVs [86]), demanding new computational approaches to accomplish. It is unlikely that a single variant or gene would greatly impact non-syndromic SB risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater power may be gained from combining gene enrichment by deleterious variants along with damaging structural variation (e.g. CNVs [86]), demanding new computational approaches to accomplish. It is unlikely that a single variant or gene would greatly impact non-syndromic SB risk.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies of the more prevalent structural birth defects like CHD have indicated that, while sequence variants that are common in human populations probably contribute to birth defects, they account for only a small proportion of genetic risk [66], so that genome wide association studies (GWAS) will require thousands of subjects to identify factors. Nevertheless, NTD cases display significant enrichment in rare variants [16, 86], suggesting these changes have greater effect sized and may be identifiable in smaller cohorts, This is the first multicenter SB case-control study to mount a comprehensive, ancestry-matched whole genome sequence (WGS) analysis from a systems biology perspective. This study seeks to identify pathways and biological functions that are disrupted in SB as reflected in their enrichment with genes or regulatory regions harboring rare, likely damaging mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Our genome-wide investigations of exonic sequences established a threshold model of ultra-rare singleton loss of function variant (SloV) burden, replicated in three different populations, that found on average 9 SloVs per individual with SB, compared to 15 SloVs per genome in individuals with anencephaly . We recently reported an initial investigation of SVs through analysis of WGS from two ancestry balanced case-control cohorts (Wolujewicz et al, 2021). The study used a computational ensemble approach to identify copy number variants (CNV) with a MAF < 0.01%, relying on CNVs that met "high confidence" criteria.…”
Section: These Investigators Usedmentioning
confidence: 99%
“…A total of 140 case samples with isolated spina bifida (myelomeningocele) which recently reported in our paper (Wolujewicz et al, 2021) were collected from California, USA and Doha, Qatar. Cases with no other anomalies, only minor anomalies or related anomalies were considered isolated.…”
Section: Human Subjectmentioning
confidence: 99%